Efficacy of Crude Soya oil and Emulsifier in Ration on Production Performance of Broilers - Srinivasan, G.; Nathan, N. Arul; Thanaseelaan, V.; Nanthini, A. Ruba (Indian Journal of Animal Nutrition, 2020)
This study was conducted to assess the efficacy of emulsifier in broiler ration containing crude soya oil on the production performance of broilers.Â A total of 90 day- old Vencobb 320 broiler chicks were randomly divided into 15 groups of six birds in each and five groups were allocated to each dieary treatment. Treatment groups were fed with basal diet contains crude soya oil as energy source (T1), basal diet supplemented with fat emulsifier at the rate of 250 g per metric tonne of feed (T2) and 80 kcal energy reduced from basal diet supplemented with emulsifier at the rate of 250 g per metric tonne of feed (T3). All the chicks were reared under deep litter system for 42 days. Body weight and feed intake were recorded weekly. Â Body weight (6th week) of T2 birds (2622 g) was comparable with T3 (2558 g) but was higher (P<0.05) than in T1 (2502 g). Similarly feed conversion ratio (6th week) was also similar between T3 (1.76) and T2 (1.80) birds, however T1 (1.87) had lower (P<0.05) FCR than in T3 group. Dressing percent was higher (P<0.05) in T1 (69.44) than occurred in T3 (65.47) and T2 (65.55). Abdominal fat percentage, breast meat yield and drumstick percentage, serum biochemical attributes were not different among three bird groups. The present study concluded that inclusion of emulsifier at the rate of 250 g / MT of feed containing crude soya oil with 80 kcal reduced metabolic energy improved body weight and feed conversion ratio at market age.